Social responsibility of the University, application of a measurement model - Álvarez Morales, Elsa Leuvany; De la Fuente-Anuncibay, Raquel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective of this research is to propose a model for measuring university social responsibility. For this purpose, a survey was applied to workers, teachers and students of the State Technical University of Quevedo, through a questionnaire adapted from the one developed by URSULA (Vallaeys, 2021). Likewise, the USR-URSULA self-diagnosis matrix (Vallaeys et al., 2021) was used to collect information from the authorities and directors of the UTEQ. The results indicate a medium performance and high reliability of the measuring instrument. In conclusion, the model can be used by the university.